2021
DOI: 10.1021/acs.nanolett.1c01655
|View full text |Cite
|
Sign up to set email alerts
|

Charge Density Wave Vortex Lattice Observed in Graphene-Passivated 1T-TaS2 by Ambient Scanning Tunneling Microscopy

Abstract: The nearly commensurate charge density wave (CDW) excitations native to the transition-metal dichalcogenide crystal, 1T-TaS2, under ambient conditions are revealed by scanning tunneling microscopy (STM) and spectroscopy (STS) measurements of a graphene/TaS2 heterostructure. Surface potential measurements show that the graphene passivation layer prevents oxidation of the air-sensitive 1T-TaS2 surface. The graphene protective layer does not however interfere with probing the native electronic properties of 1T-Ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 56 publications
0
13
0
1
Order By: Relevance
“…We assume electron transfer from the highly metallic substrate of bilayer graphene on SiC, which was used as the substrate in the experiments. Consistent with this assumption, recent experiments and DFT calculations for the graphene/1T-TaS 2 heterostructure also reported a charge transfer from graphene to the 1T-TaS 2 layer: the work function of graphene/1T-TaS 2 was found to exhibit a change of 102 ± 2 meV in Kelvin probe force microscopy, 25 and the Dirac point of graphene shifted toward a higher energy of 300 meV in the STS and DFT, indicating the hole doping. 26 In order to validate this, we examine the doping effect of a graphene substrate for a monolayer 1T-NbSe 2 in a 13 13 × structure as the simplest model as well as a more realistic substrate of BGR/SiC(0001).…”
Section: Resultsmentioning
confidence: 56%
“…We assume electron transfer from the highly metallic substrate of bilayer graphene on SiC, which was used as the substrate in the experiments. Consistent with this assumption, recent experiments and DFT calculations for the graphene/1T-TaS 2 heterostructure also reported a charge transfer from graphene to the 1T-TaS 2 layer: the work function of graphene/1T-TaS 2 was found to exhibit a change of 102 ± 2 meV in Kelvin probe force microscopy, 25 and the Dirac point of graphene shifted toward a higher energy of 300 meV in the STS and DFT, indicating the hole doping. 26 In order to validate this, we examine the doping effect of a graphene substrate for a monolayer 1T-NbSe 2 in a 13 13 × structure as the simplest model as well as a more realistic substrate of BGR/SiC(0001).…”
Section: Resultsmentioning
confidence: 56%
“…As shown in Figure 4a, the oscillation lines converge toward around V g = 300 V. We found this large CNP (charge neutrality point) shift is in accordance with the charge transfer due to the difference of work functions between graphene and 1T-TaS 2 . 29 This clear tendency shows that the resistivity peak centered at V g = −20 V is not the charge neutrality point of graphene. The charge neutrality point exists beyond the plus gate voltage range we applied.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The heterostructure of 1T-TaS 2 and a semiconductor such as black phosphorus or MoS 2 shows added characteristics of Coulomb blockade or Raman spectra results, respectively, due to the interfacial interaction. , There is an experimental result that confirmed whether the CDW order survives when the 1H-NbSe 2 CDW material is placed on various substrates including bilayer graphene, monolayer boron nitride, Au(111), and WSe 2 . In the graphene/1T-TaS 2 system, people measured a CDW phase transition of 1T-TaS 2 vertically using the few-layer graphene as electrodes and others conducted a scanning tunneling microscopy and spectroscopy using the graphene as a protective layer to hinder the oxidation of 1T-TaS 2 surface. They found that the NCCDW domain hosts topological vortices. Although there exist relevant examples of graphene and the 1T-TaS 2 integrated system, the Hall bar shape accurate transport properties of graphene influenced by the CDW phase in 1T-TaS 2 located nearby remain unexplored.…”
Section: Introductionmentioning
confidence: 98%
“…1T-TaS 2 is known to oxidize in ambient conditions, 22,23 and thus, previous STM experiments on bulk 1T-TaS 2 have typically relied upon in situ cleaving of crystals to expose a clean surface. 24−27 In this work, the exfoliated ultrathin samples measured were fabricated using a polymer transfer technique under an inert atmosphere and were only exposed to air prior to being loaded into the STM (∼5 min).…”
mentioning
confidence: 99%
“…1T-TaS 2 is known to oxidize in ambient conditions, , and thus, previous STM experiments on bulk 1T-TaS 2 have typically relied upon in situ cleaving of crystals to expose a clean surface. In this work, the exfoliated ultrathin samples measured were fabricated using a polymer transfer technique under an inert atmosphere and were only exposed to air prior to being loaded into the STM (∼5 min). While residues remained from processing the device, clean regions of interest were located and imaged by first mapping out a navigational path that avoided existing surface contamination.…”
mentioning
confidence: 99%